Board independance and the efficiency of internal capital markets - Dah, Mustafa A. (2017)
The Sarbanes-Oxley Act of 2002 and exchange listing requirements led to an increase in the percentage of independent members on company boards. The literature offers mixed evidence on the effect of board independence on corporate governance. Independent directors are said to improve the monitoring role of the board of directors. However, the presence of independent directors increases costs associated with information asymmetry and free riding problems. Accordingly, the firm's board monitoring efficiency is expected to have a significant impact on managerial decisions and the allocation of the firm's scarce resources across the different firm segments. We investigate the effect of increased board independence on the efficiency of internal capital markets in diversified firms. Data is collected from the Compustat, ExecuComp, and RiskMetrics databases. Sample is split into 2 sub-periods: (i) Pre-SOX (1996 – 2001); and (ii) Post-SOX (2003-2008). We also divide our sample into two subsamples: (i) Firms that were not in compliance with the independence requirements prior to SOX and became complying afterwards; and (ii) Firms that were already in compliance with the new requirements before SOX. We employ Berger and Ofek's (1995) method by calculating the imputed values of a given firm's segments and comparing the sum of those values to the value of the firm. Internal capital market efficiency is measured following Rajan, Servaes, and Zingales (2000). We find that the increase in board independence post-SOX may have moved firms away from their optimal board structure. Our results suggest that, relative to the pre-SOX period, increased board independence post-SOX had a negative effect on diversified firms' excess value and internal capital market efficiency. The results apply to both subsamples: (i) firms that were previously compliant; and (ii) those that weren't compliant with the mandates. This suggests that firms may not have benefited from the move towards higher independence in the post-SOX era. Mutual back scratching and socialization within the firm may explain the ineffectiveness and inefficiency of increased board independence in diversified firms. The passed legislations may have had a converse effect on corporate boards. Our results are consistent with Linck, Netter, and Yang (2008) who propose that a one-size-fits-all regulation may be inefficient and could move firms away from their optimum board composition.